Qualitative study to identify ethnicity-specific perceptions of and barriers to asthma management in South Asian and White British children with asthma. Issue 2 (8th February 2019) - Lakhanpaul, Monica; Culley, Lorraine; Huq, Tausif; Bird, Deborah; Hudson, Nicky; Robertson, Noelle; McFeeters, Melanie; Manikam, Logan; Johal, Narynder; Hamlyn-Williams, Charlotte; Johnson, Mark R D
Abstract : Objective: This paper draws on the data from the Management and Interventions for Asthma (MIA) study to explore the perceptions and experiences of asthma in British South Asian children using semi-structured interviews. A comparable cohort of White British children was recruited to identify whether any emerging themes were subject to variation between the two groups so that generic and ethnicity-specific themes could be identified for future tailored intervention programmes for South Asian children with asthma. Setting: South Asian and White British children with asthma took part in semi-structured interviews in Leicester, UK. Participants: Thirty three South Asian and 14 White British children with asthma and aged 5–12 years were interviewed. Results: Both similar and contrasting themes emerged from the semi-structured interviews. Interviews revealed considerable similarities in the experience of asthma between the South Asian and White British children, including the lack of understanding of asthma (often confusing trigger with cause), lack of holistic discussions with healthcare professionals (HCPs), an overall neutral or positive experience of interactions with HCPs, the role of the family in children's self-management and the positive role of school and friends. Issues pertinent to South Asian children related to a higher likelihood of feeling embarrassed and attributing physical activity to being a trigger for asthma symptoms. Conclusions: The two ethnicity-specific factors revealed by the interviews are significant in children's self-management of asthma and therefore, indicate the need for a tailored intervention in South Asian children.